Optimizing motor capacity in volleyball, at the level of juniors, through specific training - Cojocaru, A.-M.; Cojocaru, M. (Science, Movement & Health, 2020)
Problem. In the specific training of the player and the team, the strategy represents the specificity of the process approach, the set of objectives, the main ways of achieving them, the human and material resources involved in order to obtain superior performances. Objective. Determining the viability of our approach starting from the coordinates that characterize the initial level of specific motor capacity, including the level of training of the subjects included in the research and the verification of the means, methods and efficiency of the applied work programs. Methods. In the experiment we followed the evolution of two samples consisting of 12 volleyball players -members of the junior team of the Technical College Mihai I in Bucharest, respectively 12 volleyball players operating at the same competitive level - within the CS Dinamo Bucharest team and we used, bibliographic documentation; interpretation of statistical and mathematical method; graphical representation method.Results.It is observed that the specific motor skills register value increases, with a more significant progress in the experiment group -reflected by the significant differences registered between the averages of the two groups at the final test. Conclusions. The hypothesis is confirmed according to which the optimization of the training model, by applying specific technical-tactical structures on the game phases, can lead to the increase of the athletes' motor baggage and implicitly to the extension of the efficient expression capacity during the game, thus contributing to the performance objectives. of teams.